2014
DOI: 10.1111/cuag.12040
|View full text |Cite
|
Sign up to set email alerts
|

NERICA Upland Rice: Seeds of Change for Female‐Headed Households in Uganda?

Abstract: Recognizing that the adoption of new agricultural technology has different effects on different types of households and social actors, this study examines how femaleheaded households growing New Rice for Africa (NERICA) upland rice in Hoima District, Uganda, compare with male-headed NERICA grower households with respect to the production, productivity, and marketing of the crop. We show that NERICA has become an important cash income earner for both household categories, which obtain similar levels of producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Our review was focused on distributions of impacts among rural households, but it is important to note that impact differentiation can also occur within households, for instance when labour burdens disproportionally befall female household members (Mullins et al 1996;Doss 2001). The studies identified within the limits of our search considered households mostly as homogeneous units, although a few of the selected studies pointed out that female farmers tended to be poorer than male farmers within each of the recognized welfare classes (Lodin et al 2014;Van Vugt et al 2018;Franke et al 2019). Intra-household and gendered differentiation were beyond the scope of this study, but ostensibly require attention in further research on impact differentiation (Beuchelt 2016;Theis et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review was focused on distributions of impacts among rural households, but it is important to note that impact differentiation can also occur within households, for instance when labour burdens disproportionally befall female household members (Mullins et al 1996;Doss 2001). The studies identified within the limits of our search considered households mostly as homogeneous units, although a few of the selected studies pointed out that female farmers tended to be poorer than male farmers within each of the recognized welfare classes (Lodin et al 2014;Van Vugt et al 2018;Franke et al 2019). Intra-household and gendered differentiation were beyond the scope of this study, but ostensibly require attention in further research on impact differentiation (Beuchelt 2016;Theis et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Some models explored options for the re-allocation of land, labour, and inputs within a farm, to test which configurations maximize benefits-and found wide impact disparities due to differences in scale (Leonardo et al 2018;Michalscheck et al 2018). In the studies of Franke et al (2019) and Lodin et al (2014), rural households of different welfare levels had access to similar land areas on average, but within each welfare level, female farmers had access to smaller plots. For that reason, their total production was less, despite the female farmers obtaining similar yields as the male farmers.…”
Section: Farm and Household Levelmentioning
confidence: 99%
“…Furthermore, although we capture the effect of PPT adoption on child investment, we do not explore its effect on child labor and school attainment. Children in SSA provide substantial labor to farming, which may compromise their school attendance, performance and education attainment (Admassie, 2002;Lodin et al, 2014). Thus, additional survey data with questions aimed at understanding child labor, school attendance, and performance would also be important.…”
Section: Discussionmentioning
confidence: 99%
“…In recent work, Lodin et al (2014) sought to establish at what and whose cost rice farming was made more productive and profitable with the adoption of NERICA rice varieties in Uganda. The study revealed that the costs of technology adoption fell largely on women and children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation